The Relationship Between Postpartum Depression and Beliefs About Motherhood and Perfectionism During Pregnancy - Anja, Wittkowski; Charlotte, Garrett; Alison, Cooper; Angelika, Wieck (Journal of Women's Reproductive Health, 2017)
Postpartum depression is a common mood disorder following childbirth. Depression occurring at this crucial stage in a child’s life is known to have far reaching and potentially damaging consequences for the mother, the baby and her family. Whilst a number of risk factors have been identified in the literature as contributing to the development of postpartum depression, including a past psychiatric history and lack of social support, some of these are not easily modifiable through psychological interventions. The aim of this longitudinal study was to examine the contribution of specific psychological factors, including maternal beliefs about motherhood and perfectionism and perceived social support, in the development of postpartum depression. Seventy-three pregnant women consented to take part and returned questionnaires during the third trimester of their pregnancy. Of those women, 61 also completed questionnaires 4-6 weeks following the birth of their baby. Significant associations were identified for postpartum depression and the psychological variables of perfectionistic beliefs and social support, whereas many demographic factors were not significantly implicated in the development of depression. Using a multiple hierarchical regression analysis, the study examined whether maternal beliefs about motherhood and beliefs about perfectionism predicted more of the variance in postpartum depression scores than other demographic variables, including a past history of emotional difficulties. As predicted, beliefs about motherhood and perceptions of poor social support from friends and family were significant predictors of postpartum depression, when the influence of antenatal depression scores were accounted for. A past history of emotional difficulties was also retained in the final model, whereas beliefs about perfectionism were not. These findings have implications for clinical services, highlighting the need for refined assessments of expectant mothers’ beliefs about motherhood and their perceptions of their social support during pregnancy and the need for more refined psychological interventions that address these beliefs.
Keywords: Motherhood; pregnancy; beliefs; cognitions; postpartum depression; women; perfectionism.